Students who are both victims and perpetrators of physical violence at a private high school in rural North Vietnam: Prevalence and Socio-Demographic Correlates - Nguyen Ngoc, Binh; Le Thi Kim, Anh; Truong Quang, Dat (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Backgrounds: Physical violence in schools is a fairly common problem in Vietnam. However, current studies pay little attention to violence in private schools. Objectives: The study aims to estimate the prevalence and related sociodemographic factors of school physical violence among students at Hiep Hoa 5 private high school in Bac Giang province in Northern Vietnam. Methods: This was a school-based cross-sectional survey using a random sample technique with a multistage process from April to June 2019. Main findings: 412 students participated in the study, and the results indicated that 55/412 (13.3%) students were both perpetrators and victims of school violence. While 16.7% of students performed physical violence, 27.9% of students suffered physical violence by other students in the past six months. Experiencing physical violence was associated with sociodemographic characteristics such as gender, grade, exposure to physical violence in the media, time playing action games and witnessing violent events in the living place.. Conclusions: More than 13% of students are perpetrators and victims of physical violence by their peers at a rural private high school. This prevalence is significantly correlated with individual factors. The results suggest that a greater focus on young people's educational activities should be provided to direct their development, including preventing physical violence.